Human factor risk management procedures applied in the case of open pit mine. (August 2021) - Kirin, Snezana; Sedmak, Aleksandar; Li, Wei; Brzaković, Miodrag; Miljanović, Igor; Petrović, Ana; Sedmak, Simon
Highlights: Application of risk analysis in structural integrity assessmen. Case studies involving real failures of mining equipment. Combination of analytical and numerical methods. Significance of the human factor on structural integrity and safety. Abstract: Risk management aims to provide a controlled work environment to ensure the safe operation of the high-risk systems. It is a dynamic process which work in a continual state of change. The issue of human factor risk and rules and regulations in open pit mine is a main focus of this paper in order to develop predictive models of behavior of workers in relation to compliance with the procedures and rules. Presented survey was conducted in open pit coal mine, as high-risk system, involving 476 mineworkers. The survey was in the form of a questionnaire, consisting of approximately 45 questions. It aimed to find out the opinions of the mining workforce about risk attitude generally as well as about safety rules and regulations. The first goal was to determine factor with the biggest influence on risk of human factor. The second goal was creation model for prediction behavior of mining workers. The survey also aimed to examine: (a) major human risk factors at a specific open-pit mine site (b) mine workers' opinions about policies and procedures; (c) the manner in which mine safety rules and regulations are perceived and understood; (d) the frequency of deviation from rules and regulations; (e) attitudes related to risk taking and their interaction with rules and regulations; and (f) anticipate the behavior of mining workers with respect to compliance with policies and procedures. In addition, a case study is presented, related to failure of mining equipment, the SchRs 630 bucket wheel excavator, which had occurred due to excessive loads caused by a human factor, such as inadequate operation of the equipment. The goal here was to further relate the effects of the human factor to the structural integrity, by providing a reliable numerical model which could be used to determine the critical locations where failures could occur, and by combining this approach with the previously described risk analysis methodology, structure safety can be improved.